Methylcitrate cycle defines the bactericidal essentiality of isocitrate lyase for survival of Mycobacterium tuberculosis on fatty acids - Eoh, Hyungjin (National Academy of Sciences, 2014)
Few mutations attenuate Mycobacterium tuberculosis (Mtb) more profoundly than deletion of its isocitrate lyases (ICLs). However, the basis for this attenuation remains incompletely defined. Mtb’s ICLs are catalytically bifunctional isocitrate and methylisocitrate lyases required for growth on even and odd chain fatty acids. Here, we report that Mtb’s ICLs are essential for survival on both acetate and propionate because of its methylisocitrate lyase (MCL) activity. Lack of MCL activity converts Mtb’s methylcitrate cycle into a “dead end” pathway that sequesters tricarboxylic acid (TCA) cycle intermediates into methylcitrate cycle intermediates, depletes gluconeogenic precursors, and results in defects of membrane potential and intrabacterial pH. Activation of an alternative vitamin B(12)-dependent pathway of propionate metabolism led to selective corrections of TCA cycle activity, membrane potential, and intrabacterial pH that specifically restored survival, but not growth, of ICL-deficient Mtb metabolizing acetate or propionate. These results thus resolve the biochemical basis of essentiality for Mtb’s ICLs and survival on fatty acids.